KOZAKLAR: MİLLİ KİMLİK VE SOSYO-KÜLTÜREL YAŞAM - Erdoğan, Hanife (Motif Akademi, 2020)
The Cossacks, who occupy an important place in the history of Russia, are a people providing military service in the border regions and emerging as their warrior identities. The Cossacks are named, according to the geography they distribute, as Don Cossacks, Terek Cossacks, Siberian Cossacks, Ural Cossacks, Amur Cossacks, Ussuriysk Cossacks, Kuban Cossacks etc. The origin and ancient history of the Cossacks are contradictory and there is no consensus. In this study, on being given the meaning and origin of the Word Cossack besides the theories put forward about the emergence of the Cossacks; It is aimed to give general information about the social life, housing, kitchen, traditional clothes and education of the Cossacks. Apart from the warrior spirit of the Cossacks, social life, family structure and other factors have also become a point of interest. Apart from fighting, the Cossacks were interested in agriculture, hunting and fishing. Having a rich cuisine culture, the Cossacks did not skimp on feasting especially on important days such as baptism, name days and weddings. The effect of the Russian and Turkish states was observed when the Cossack traditional dresses were examined in general. In the context of education, martial art and military disciplines came to the fore. In educational institutions, the aim was not only teaching literacy, but also preparing young people for military service.

Rusya tarihinde önemli yer tutan Kozaklar, sınır bölgelerinde askerlik hizmeti veren ve savaşçı kimliğiyle ortaya çıkan bir halktır. Kozakların kökeni ve kadim tarihi çelişkili olup, ortak bir görüşe varılamamıştır. Kozaklar, dağılım gösterdikleri coğrafyaya göre Don Kazakları, Terek Kazakları, Sibirya Kazakları, Ural Kazakları, Amur Kazakları, Ussuriysk Kazakları, Kuban Kazakları vs. olarak adlandırılmıştır. Bu çalışmada Kozak sözcüğünün anlamı ve kökeni ayrıca Kozakların ortaya çıkışı ile ilgili öne sürülen kuramların verilmesinin ardından; Kozakların sosyal yaşamı, konutları, mutfağı, geleneksel giysileri ve eğitimi çerçevesinde genel bilgi verilmesi amaçlanmıştır. Kozakların savaşçı ruhunun dışında sosyal yaşamları, aile yapısı gibi unsurlar da merak noktası olmuştur. Kozaklar savaşmak dışında tarım, avcılık ve balıkçılıkla ilgilenmişlerdir. Zengin bir mutfak kültürüne sahip olan Kozaklar özellikle vaftiz, isim günü ve düğün gibi önemli günlerde ziyafet vermeyi eksik etmemişlerdir. Kozakların geleneksel kıyafetlerine genel olarak bakıldığında ise Rusların ve Türk devletlerinin etkisi gözlemlenmiştir. Eğitim bağlamında ise savaş sanatı ve askerî disiplinler öne çıkmıştır. Eğitim kurumlarında sadece okuma- yazma öğretme amacı güdülmemiş, aynı zamanda gençleri askerlik hizmetine hazırlama amacı da güdülmüştür.
Keywords: Cultural Studies; The Cossacks; warrior identity; social life; cuisine culture; traditional dress; Kültürel çalışmalar; Kozaklar; savaşçı kimlik; sosyal yaşam; mutfak kültürü; geleneksel kıyafet